An easy platform for calculating biodiesel yield with a graphical user interface - Al Afghani, Fajar; Tri Atmaja, Sigit; Nurdam, Nofriyadi; Sulistia, Susi; Sampora, Yulianti; Fahmiati, Sri; Irawan, Yan; Ndruru, Sun Theo Constan Lotebulo; Wihadi, Muh. Nur Khoiru; Sofyan, Muhammad Ihsan (Science, Engineering and Health Studies, 2025)
An algorithm for calculating the biodiesel yield from esterification/transesterification was developed. The algorithm was represented in a program to facilitate researchers in exploring different types of feedstocks and catalysts. The input program of the preliminary yield data was processed numerically to generate reaction rate constant (k), reaction order (n), and activation energy (Ea) as a part of the kinetics response. The study revealed that the transesterification of used cooking oil and methanol with 0.25 wt% KOH catalyst had pseudo-first-order kinetics, with Ea = 21.7 kJ/mol. The optimum % yield obtained through the calculation was 96.5% at 323 K (50°C) within 10 h of reaction time. This program succeeded in validating secondary data from experimental research with a tolerance level of 10–17%. The program was validated where the model accuracy (R2) for the first and second validations were 0.90 and 0.98, respectively. The application of this program is not limited to a specific biodiesel reaction design and can be extended to other designs as well.